Values and their relationship with emotion processing and physical and psychological symptoms among Jewish and Arab breast cancer survivors - Hebi, Maimounah; Czamanski-Cohen, Johanna; Azaiza, Faisal; Weihs, Karen L. (Frontiers in Psychology, 2024)
Introduction Individuals from different cultures differ in their values, which encompass belief systems that individuals develop based on their culture, and play a pivotal role in shaping their perspectives. These values may affect emotion processing (EP): the recognition, interpretation, expression and response to bodily sensations, translated as emotions. These varying values may contribute to distinct emotional experiences, impacting physical and psychological symptoms in breast cancer (BC) survivors. Methods This cross-sectional study investigated how EP including acceptance, expression (avoidance and approach coping), and awareness, may mediate the relationship between conservation values and symptoms of pain, fatigue, and depression among Arab (n = 62) and Jewish (n = 179) women BC survivors in Israel. Conservation values include tradition, conformity, and security. Results Depression and fatigue were negatively correlated with acceptance of emotions, and positively correlated with avoidance and conservation levels. Emotion processing mediated the relationship between conservation and fatigue and depression. Arab women reported higher levels of various values, emotional acceptance, pain, fatigue, and depression symptoms compared to Jewish women. Conservation was higher in Arab women and correlated with both approach and avoidance coping which was not the case in Jewish women. Avoidance coping had a positive relationship with fatigue in the Jewish, but not the Arab women. Similarly, approach coping was negatively related to depression in Jewish, but not in Arab women. Discussion Cultural differences are important for understanding the experience of cancer in individuals from different cultures. Future interventions for more conservative BC survivors should take culture into account.